Management of Vesicouterine fistulae during fistulae surgical caravan in Cote d'Ivoire - L. E., Djanhan; J. M., Dia; M. M., Menin; E., Bohoussou; B., Kouamé; Y., Samaké; K. P., Kouakou; Y., Doumbia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The urogenital fistula (UGF) which designate a solution of continuity between the urinary and genital tracts in women, are divided into several entities of variable gravity. The objective of this study was to describe the epidemiological, clinical and therapeutic characteristics of patients treated for vesicouterine fistula during ‘fistulas surgical caravans’. Methods: This was a prospective and descriptive study on a cohort of 34 patients treated for Vesico-uterine fistulae during ‘‘fistulas surgical caravans '' from 1st January 2012 to 31st December 2016. Results: Vesico uterine fistulae represented 2.1% of all urogenital fistulae treated. At the time of occurrence of fistulas, the average age of the patients stay was 33.3 years, and the majority was not educated (88.2%), lived in rural areas without occupations (73.5%). All the fistulae were secondary to childbirth, the majority of which took place on a scarred uterus (67.6%). And this childbirth responsible for the fistula was done by caesarean section in 97.7% of cases. Then the average duration of the fistula before management was 6 years. Finally, all the patients were operated by the same surgical technique, made by abdominal extra peritoneal transvesical way. The cure rate after this surgical technique was 97.1% (33 patients). The only case of failure required a second operation by another technique which permitted the healing of the patient. Conclusions: The vesicouterine fistulae were rare and the satisfactory results of their management invite us to sustain these surgical caravans and ensure their widespread.